2023
DOI: 10.3390/jof9030315
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Aspergillosis in Critically Ill COVID-19 Patients Admitted to the Intensive Care Unit: A Retrospective Cohort Study

Abstract: COVID-19-associated pulmonary aspergillosis (CAPA) is a life-threatening fungal infection that mainly affects critically ill patients. The aim of this study was to assess the incidence and clinical outcomes of putative CAPA in critically ill COVID-19 patients. This retrospective observational cohort study included 181 cases from 5 ICUs at Vienna General Hospital between January 2020 and April 2022. Patients were diagnosed with putative CAPA according to the AspICU classification, which included a positive Aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Their analysis included critically ill cases and those with mixed populations. The proportion of fungal coinfections was reported, and the mortality rate associated with fungal coinfections and COVID-19 was determined (25,51,55). The overall mortality rate was found to be 10.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Their analysis included critically ill cases and those with mixed populations. The proportion of fungal coinfections was reported, and the mortality rate associated with fungal coinfections and COVID-19 was determined (25,51,55). The overall mortality rate was found to be 10.9%.…”
Section: Discussionmentioning
confidence: 99%
“…CAPA onset is more delayed compared to IAPA; usually, the onset is >7 days from ICU admission (median 8 days, IQR 5–15), although a study that used a strategy of performing a BAL directly after admission reported an earlier onset (4 days) [5,44 ▪▪ ,49,50 ▪▪ ,51,52 ▪▪ ]. It should be highlighted though, that the true prevalence of CAPA and the timing of onset remains to be further defined, as most studies relied on diagnostic work up either on deteriorating patients or on positive upper respiratory tract cultures [5,44 ▪▪ ].…”
Section: The History Of Risk Profiles: Broadening Risk Profile and Im...mentioning
confidence: 99%
“…Compared with COVID-19 cases that are not complicated by IPA, CAPA is associated with worse outcomes overall, as well as in the subgroup of patients requiring extracorporeal oxygenation (ECMO) [5,49,50 ▪▪ ,51]. The mortality of CAPA is high, but with a wide reported range, from 36% to 74% [5,49,50 ▪▪ ,51]. The attributable mortality of CAPA is not fully elucidated [45 ▪▪ ].…”
Section: The History Of Risk Profiles: Broadening Risk Profile and Im...mentioning
confidence: 99%
“… 2 Aspergillosis poses a significant public health threat, especially among immunocompromised individuals and patients receiving intensive care, with mortality rates surpassing 50%. 3–5 …”
Section: Introductionmentioning
confidence: 99%